Sustainable production of biomass and biodiesel by acclimation of non-acidophilic microalgae to acidic conditions. (January 2019) - Abinandan, Sudharsanam; Subashchandrabose, Suresh R.; Cole, Nicole; Dharmarajan, Rajarathnam; Venkateswarlu, Kadiyala; Megharaj, Mallavarapu
Graphical abstract: Highlights: Two strains of non-acidophilic microalgae (NAM) were acclimated to pH 3.0. Flow cytometry analysis indicated their ability to withstand acidic pH. Both the acclimated strains yielded good amounts of biomass and neutral lipids. FTIR analysis confirmed accumulation of more triacylglycerols in NAM strains. First report on biodiesel production in good amounts by NAM strains at pH 3.0. Abstract: The overwhelming response towards algal biodiesel production has been well-recognized recently as a sustainable alternative to conventional fuels. Most microalgae cannot grow well at acidic pH. The present study, therefore, investigated whether non-acidophilic microalgae Desmodesmus sp. MAS1 and Heterochlorella sp. MAS3 can be acclimated to extreme-acidic pH for sustainable production of biomass and biodiesel. Growth analysis indicated that both the microalgal strains possessed a passive uptake of CO2 at pH 3.0 with biomass production of 0.25 g dry wt. L −1 in Desmodemus sp. and 0.45 g dry wt. L −1 in Heterochlorella sp.. Flow-cytometry analysis for reactive oxygen species, membrane permeability and neutral-lipids revealed the capabilities of both strains to adapt to the stress imposed by acidic pH. Lipid production was doubled in both the strains when grown at pH 3.0. In-situ transesterification of biomass resulted in 13–15% FAME yield in the selected microalgae, indicating their great potential in biofuel production.